Building Health Literacy and Cultural Competency Through Video Recording Exercises - Brian Henriksen; Jennifer Henriksen; J. Scott Thurston (University of Minnesota Libraries Publishing, 2016)
Video creation skills would allow pharmacists to create content tailored to their patients' needs and include relevant aspects of cultural competency to achieve the goal of improved health literacy. Video recording exercises can provide students with an opportunity to build their drug knowledge and health literacy skills. Conflict of Interest None   Type: Commentary